ANALYSIS OF TEACHING AND WAGE INFORMATION SYSTEMS AS INTERNAL CONTROL TOOLS IN ABC COMPANIES IN MADIUN - Antika Dewi; Supri Wahyudi Utomo; Liana Vivin Wihartanti (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
This study intends to analyze internal control efforts in the payroll and wage accounting information system carried out by the company in the area. The method used is a qualitative approach using interviews and documentation relating to payroll and wages for company employees in the area. The results show that the accounting information system used for employee payroll and wages is following the procedure and can be said to be effective because of the flow diagram and overtime process which are not by the SOP. Internal control carried out on companies in Madiun has not been effective because there are multiple tasks and a lack of employee monitoring.